2021
DOI: 10.1073/pnas.2022977118
|View full text |Cite
|
Sign up to set email alerts
|

Cloud shadows drive vertical migrations of deep-dwelling marine life

Abstract: Many zooplankton and fishes vertically migrate on a diel cycle to avoid predation, moving from their daytime residence in darker, deep waters to prey-rich surface waters to feed at dusk and returning to depth before dawn. Vertical migrations also occur in response to other processes that modify local light intensity, such as storms, eclipses, and full moons. We observed rapid, high-frequency migrations, spanning up to 60 m, of a diel vertically migrating acoustic scattering layer with a daytime depth of 300 m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 56 publications
1
28
0
Order By: Relevance
“…Light is considered the dominant proximate cue for DVM 14 , 18 with animals commonly staying below a changing depth of threshold light intensity termed the isolume 18 . Depth adjustment is often closely connected to light intensity with organisms rapidly responding to solar and lunar light sources 19 , 20 , as well as short-term irradiance changes from cloud cover 21 , phenomenological 22 and anthropogenic events 23 . Furthermore, the migration behavior is often under some degree of circadian clock control imparting an innate cue to migrate when environmental signals may be damped, masked, or absent 18 , 24 .…”
Section: Resultsmentioning
confidence: 99%
“…Light is considered the dominant proximate cue for DVM 14 , 18 with animals commonly staying below a changing depth of threshold light intensity termed the isolume 18 . Depth adjustment is often closely connected to light intensity with organisms rapidly responding to solar and lunar light sources 19 , 20 , as well as short-term irradiance changes from cloud cover 21 , phenomenological 22 and anthropogenic events 23 . Furthermore, the migration behavior is often under some degree of circadian clock control imparting an innate cue to migrate when environmental signals may be damped, masked, or absent 18 , 24 .…”
Section: Resultsmentioning
confidence: 99%
“…However, the factors affecting the scattering layer may be different in different regions, such as cloud shadows, moonlight conditions, and tidal dynamics, which may also affect the DVM. Omand et al [43] revealed that cloud shadows in subpolar seas drive variability in surface photosynthetically available radiation, leading to vertical migration of zooplankton above 300 m. Last et al [44] showed that changes in moonlight can drive the DVM during the Arctic winter, presumably because moonlight affects the predator-prey interactions. However, Petrusevich et al [45] found tidal dynamics, not moonlight, to play an important role in the DVM of the scattering layer in Hudson Bay, which is unlike polar and subpolar oceans.…”
Section: Echo-integrationmentioning
confidence: 99%
“…where ∆w 0 denotes the induced velocity at the center of the aggregation position. When available, estimates for ∆w 0 can be obtained from in situ measurements [43][44][45] or estimated a priori from animal and aggregation parameters following the methodology of Houghton [46] (see Eq. 38 in Supplementary Materials [37]).…”
mentioning
confidence: 99%
“…Detectability of biogenic signatures-To assess the feasibility of detecting these magnetic signatures, representative values for each physical parameter are chosen and substituted for the dimensionless variables. Using B geo = 25µT [47], ς 0 = 25 m [13], σ = 5 S/m, and W = 2 cm • s −1 [43][44][45], the nominal scale of the vertical magnetic signature for the high aspect ratio model gives R m B y = µ 0 σW ς 0 B y = 79 pT. Recasting the data from the high aspect ratio model in terms of these parameters gives the distributions shown in Figs.…”
mentioning
confidence: 99%
See 1 more Smart Citation